2020
DOI: 10.20473/jmv.vol3.iss2.2020.203-207
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Probiotik Terhadap Feed Efficiency dan Egg Mass pada Ayam Petelur

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui penggunaan probiotik yang mengandung Enterobacter sp., Cellulomonas sp., Actinomyces sp., Bacillus sp., dan Lactobacillus sp. terhadap feed efficiency dan egg mass pada Ayam Petelur. Sebanyak 36 ekor ayam petelur umur 30 minggu yang terdiri dari 3 perlakuan.  Perlakuan terdiri dari P0 (tanpa probiotik), P1 (probiotik 1 ml/liter), P2 (probiotik 2 ml/liter). Hasil penelitian pemberian probiotik berpengaruh (p<0.05) terhadap feed efficiency dan egg mass. Pembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The use of probiotics in quail through feed and water is expected to improve the efficiency of feed and increase egg production [40]. The results of this study are also in line with research by Mas'ad et al [41], who reported that the treatment group given additional probiotics in drinking water gave better results compared to the control group. The results of this study are in accordance with research conducted by Pradikta et al [42], who reported that the value of egg mass increases as the amount of probiotics for laying hens increases.…”
Section: Egg Masssupporting
confidence: 90%
See 2 more Smart Citations
“…The use of probiotics in quail through feed and water is expected to improve the efficiency of feed and increase egg production [40]. The results of this study are also in line with research by Mas'ad et al [41], who reported that the treatment group given additional probiotics in drinking water gave better results compared to the control group. The results of this study are in accordance with research conducted by Pradikta et al [42], who reported that the value of egg mass increases as the amount of probiotics for laying hens increases.…”
Section: Egg Masssupporting
confidence: 90%
“…The results of this study are also in line with research by Mas’ad et al . [ 41 ], who reported that the treatment group given additional probiotics in drinking water gave better results compared to the control group. The results of this study are in accordance with research conducted by Pradikta et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased feed efficiency will result in increased consumption of nutrients, one of which is protein which plays a role in increasing the growth of chickens (Hamid et al, 2022). Feed efficiency is influenced by several factors, not only by the physiological and genetic conditions of the animal but also by the microbes in the gut (Mas'ad et al, 2020). Microbes in the intestinal tract can affect nutrient digestion and energy absorption (Lokapirnasari et al, 2019).…”
Section: Feed Efficiencymentioning
confidence: 99%
“…Probiotics are feed supplements derived from live bacteria that can provide benefits to livestock in improving the balance of microflora in the digestive tract so that it is useful in increasing the digestibility of the rumen of livestock or microorganisms that live in a certain medium that is used to balance the digestive tract (Trimudita & Djaenudin, 2021;Siswantoro et al, 2021;Khothijah et al, 2021;Firdani et al, 2021. The use of probiotics is beneficial because it can increase livestock productivity and can reduce expenditure on feed (Solehudin et al, 2020;Sjofjan et al, 2020), for example in chickens, resulting in improved feed conversion (Megawati et al, 2020;Mas'ad et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%